2016
DOI: 10.1021/acs.jpcb.5b12233
|View full text |Cite
|
Sign up to set email alerts
|

Utility of 5-Cyanotryptophan Fluorescence as a Sensitive Probe of Protein Hydration

Abstract: Tryptophan (Trp) fluorescence has been widely used to interrogate the structure, dynamics and function of proteins. In particular, it provides a convenient and site-specific means to probe a protein’s hydration status and dynamics. Herein, we show that a tryptophan analog, 5-cyanotryptophan (TrpCN), can also be used for this purpose, but with the benefit of enhanced sensitivity to hydration. This conclusion is reached based on measurements of the static and time-resolved fluorescence properties of 5-cyanoindol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 55 publications
3
80
0
Order By: Relevance
“…Indeed, our CD results (SI Appendix, Figs. S16 and S17) show that although TPA + clusters can induce α-helix formation in an alanine-based peptide, as observed by Dempsey et al (24), they do not increase the α-helicity of a Trp3/Trp CN mutant of the antimicrobial peptide mastoparan-X that is known to form an amphipathic α-helix upon binding to the interfacial region of lipid micelles or membranes (30). These results suggest that unlike membrane-mimic micelles formed by surfactants, a single TPA + cluster is unable to provide a continuous water-hydrophobic interface large enough to host an entire α-helix.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Indeed, our CD results (SI Appendix, Figs. S16 and S17) show that although TPA + clusters can induce α-helix formation in an alanine-based peptide, as observed by Dempsey et al (24), they do not increase the α-helicity of a Trp3/Trp CN mutant of the antimicrobial peptide mastoparan-X that is known to form an amphipathic α-helix upon binding to the interfacial region of lipid micelles or membranes (30). These results suggest that unlike membrane-mimic micelles formed by surfactants, a single TPA + cluster is unable to provide a continuous water-hydrophobic interface large enough to host an entire α-helix.…”
Section: Resultsmentioning
confidence: 59%
“…To help better understand the results obtained with linear and nonlinear IR spectroscopic methods, we also performed fluorescence measurements. It has been shown that the fluorescence quantum yields of Phe CN and Trp CN are sensitive to interactions with water molecules (29,30), with a relation that hydration increases/decreases the fluorescence intensity of Phe CN / Trp CN . Thus, both unnatural amino acids can in principle be used as fluorescence probes to assess how Gdm + and TPA + affect the local hydration status of Phe CN and Trp CN in GF CN G and GW CN G. However, we only carried out fluorescence experiment on GW CN G because Cl − is known to significantly quench the fluorescence of Phe CN (29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous neutron diffraction measurements on indole/methanol/water solutions, 9 as well as with infra-red measurements on indole derivatives in solution which have been shown to be sensitive to -OH bonding to the benzene ring motifs. 31,32 From the excess entropy calculations here, this appears to be enthalpically driven rather than entropically driven given that methanol is more ordered compared with water around indole in solution and indole has a much higher solubility in methanol compared with water.…”
Section: Discussionmentioning
confidence: 85%
“…Many past studies have focused on Trp-based unnatural amino acids, including azatryptophans (5,6,12) and various indole-ring substituted analogs (13)(14)(15)(16), aiming to identify useful biological fluorophores. Whereas some Trp analogs indeed exhibit improved fluorescent properties over Trp, none of them has found broad applications due to certain photophysical limitations.…”
mentioning
confidence: 99%